Key Technology and Application of High-Speed Gearbox Used in the Integral Type Single Cantilever Centrifugal Compressor - Li Yufeng; Wu Luji; Yang Linjie; Cao Zhigang (Jixie chuandong)
The characteristics,design principles and matters need attention in the design of the high-speed gearbox used in the integral type single cantilever centrifugal compressor are mainly introduced,and this design method is successfully applied to the new product.A good effect of the gearbox reliability and improving design efficiency is obtained.